Investigating availability of cloud free images with cloud masks in relation to satellite revisit frequency in the Northwest of England - OGUNBADEWA, Ebenezer Yemi (Contributions to Geophysics and Geodesy, 2012)
The aim of this study is to determine the availability of cloud free imagesin relation to satellite revisit periods for the UK and in particular for the Northwest ofEngland. Cloud free pixels were analysed with cloud masks from AVHRR/APOLLO andTERRA/MODIS satellite cloud products. Availability of cloud free images was determinedfrom revisit frequency and the numbers of monthly images from Landsat ETM+,ASTER, Quickbird and SPOT satellite sensors series. The average number of cloud freedays at Risley Moss and Charter’s Moss is five days per month with a minimum of onecloud free day. The results show that satellite revisit periods and cloud free days area major determinant of satellite data availability and in this study it was also foundthat contrary to popular opinion, satellite overpass does not necessarily mean imagingopportunity and additional cloud free images could be obtained when there are no satelliteoverpasses. The number of cloud free images at a given site may be increased bycombining data from different satellites.